Comprehensive evaluation of urbanization development quality in Four East China Provinces. Issue 1 (December 2020) - Yang, J; Han, M M; Yao, H M; Liu, T; Wang, Y H
Abstract: Urbanization is an inevitable route to modernization for any nation, its developing level is also a major sign of the prosperity of the country. However, the development of urbanization in China is rather fast but the quality of development is not high, and there are several problems in the development of urbanization with a large number of farmers swarming into the nearby city. Therefore, the main goal of urbanization in the new era is to speed up the urbanization of agricultural transfer population and improve the construction of urban basic security system. An attempt is made in this paper to construct a new evaluation index system of urbanization, and quantitatively analyze the development quality of urbanization in Shandong, Jiangsu, Zhejiang and Guangdong provinces by factor analysis using SPSS software. It is noteworthy to mention that at present, the factors such as the education level of the transferred population and the basic guarantee system of the city are important obstacles in the development of urbanization. In view of this, several countermeasures and suggestions are put forward from four aspects viz., promoting the development of industrial integration, strengthening the construction of urban infrastructure, overall planning and improving the urban and rural security system, and speeding up the education for the whole people.